Excise Taxes with Multiproduct Transactions - Hamilton, Stephen F (American Economic Review, 2009)
I examine excise taxes levied on multiproduct retailers. Excise taxes reduce equilibrium output and decrease equilibrium product variety in the short run, but taxes can raise output per product in the long run and induce entry. Excise taxes are overshifted into prices in a wide range of cases, including under linear and concave demand conditions, and excise taxes shift less than one-for-one into prices only when demand is highly convex. Multiproduct transactions substantively alter the efficiency of ad valorem and specific forms of excise taxes and affect the comparison of relative tax performance over short-run and long-run time horizons. (JEL H25, H32, L11, L13, L81)